Cold and hot water immersion in elite youth football players: Effect on recovery of physical performance after a simulated game - Gustafsson, J.; Montiel-Rojas, D.; Edholm, P.; Johansson, E.; Romare, M.; Folkesson, M.; Venckunas, T.; Chaillou, T.; Ponsot, E. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Recovery in competitive team sport such as football is important. Cold Water Immersion (CWI) and Hot Water Immersion (HWI) have become a common practice based on the assumption that they can restore physical performance. While the use of CWI in football is well studied, there are fewer studies on HWI, or studies comparing HWI and CWI. Furthermore, it is important to account for the potential placebo effect in the design of studies assessing recovery. In this study, we investigated the effect of CWI and HWI after a simulated football match (SFM) on the recovery of physical performance in male elite youth football players.